2020
DOI: 10.3390/en13153883
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renewable Energies for the Sustainable Energy Governance and Environmental Policies for the Mitigation of Climate Change in Ecuador

Abstract: This article presents a comparative analysis of energy governance with respect to renewable energy sources in Ecuador. The use of renewable energy sources increases energy security and enables countries to achieve their climate mitigation goals. Ecuador’s energy mix is dominated using fossil fuels and produces only 7.8% of its energy supply from renewable energy. The scenario analysis suggests that using the example of international renewable energy policies will achieve sustainable energy development in Ecuad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 45 publications
1
34
1
Order By: Relevance
“…A variety of responses have been noted in the literature when analyzing the relationship between economic growth and CO 2 emissions for different countries; some studies have indicated that economic growth has a causal relationship with the variation in CO 2 emissions [17,18,20,[62][63][64][65][66][67]. Other studies indicate that there is a two-way relationship between economic growth and CO 2 emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of responses have been noted in the literature when analyzing the relationship between economic growth and CO 2 emissions for different countries; some studies have indicated that economic growth has a causal relationship with the variation in CO 2 emissions [17,18,20,[62][63][64][65][66][67]. Other studies indicate that there is a two-way relationship between economic growth and CO 2 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Prospects for global macroeconomic development must urgently take concrete political action to achieve sustained economic growth sustainably. The investigations of [11][12][13][14][15][16][17][18][19][20] establish that energy consumption is related to economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The threats resulting from the changing climate are multifaceted [12], they constitute an existential threat to many aspects of public life and the Earth's ecosystems [13,14]. Climate change affects poverty, health, the economy, infrastructure, equality and gender relations [15].…”
Section: Climate and Wellbeingmentioning
confidence: 99%
“…The turbine rotates and is connected to a generator so that it can produce electricity. System discharge efficiency is systematically written as follows [9]. 𝜂𝑑 = 𝜂𝑇 𝑥 𝜂𝐺 𝑥 𝜂𝑃 (1) For the calculation of the electrical power of the system, it is obtained using equation (2) as follows…”
Section: Discharge Processmentioning
confidence: 99%